Acute liver failure caused by occupational exposure to HCFC-123: Two case reports. Issue 9 (March 2019) - Choe, Hun Jee; Ahn, Soomin; Jung, Kwangrok; Kim, Jin-Wook
Abstract: Rationale: Hydrochlorofluorocarbon 123 (HCFC-123, Freon123; 2, 2-dichloro-1, 1, 1-trifluoroethane) has been widely used in refrigeration and heat-transfer applications as a substitute for chlorofluorocarbons due to its lower ozone-depleting potentials. Occupational exposure to HCFC-123 may cause mild reversible hepatoxicity, but no fatal cases have been reported yet. Patient concerns: In this report, we present cases of severe hepatitis with fatal outcome by HCFC-123. Two industrial workers from a manufacturing factory of fire extinguishers which use HCFC-123 were presented with diarrhea, fever, myalgia, and jaundice. Patients had been repeatedly exposed to the liquid form of HCFC-123 for the past three weeks before flare of symptoms. Diagnosis: The blood biochemistry tests showed acute cholestatic hepatitis and liver biopsy findings indicated inflammatory hepatocellular injury. The diagnosis of HCFC-123 induced hepatitis was made. Interventions: The treatment for both patients were generally supportive. The second patient went through hemodialysis, ventilatory care, and artificial liver support therapy (molecular adsorbent recirculating system) at intensive care unit. Outcomes: One patient recovered uneventfully, whereas the other patient showed rapid deterioration leading to acute liver failure complicated with cerebral edema, subdural hemorrhage, and death on hospital day 10. Lessons: The HCFC-123-induced hepatitis showed similarities with halothane hepatitis, both of which may share pathophysiologic mechanisms. Exposure to HCFC-123 needs to be listed as a potential cause of acute liver failure, and to be considered in patients with acute hepatitis of uncertain etiology and negative viral serology.